Chronic kidney disease, hypovitaminosis D, and mortality in the United States - Mehrotra, Rajnish; Kermah, Dulcie A.; Salusky, Isidro B.; Wolf, Myles S.; Thadhani, Ravi I.; Chiu, Yi-Wen; Martins, David; Adler, Sharon G.; Norris, Keith C. (Kidney international, 2009)
Low serum 25-hydroxy vitamin D (25OHD) predicts a higher cardiovascular risk in the general population. Because patients with chronic kidney disease are more likely to have low serum 25OHD, we determined the relationship between hypovitaminosis D and death in this group. Analysis was done using a cohort composed of 3011 patients from the Third National Health and Nutrition Examination Survey who had chronic kidney disease but were not on dialysis and who had a mean follow-up of 9 years. In analyses adjusted for demographics, cardiovascular risk factors, serum phosphorus, albumin, hemoglobin, stage of chronic kidney disease, albuminuria, and socioeconomic status, individuals with serum 25OHD levels less than 15ng/ml had an increased risk for all-cause mortality when compared to those with levels over 30ng/ml. This significantly higher risk for death with low serum 25OHD was evident in 15 of the 23 subgroups. The higher risk for cardiovascular and non-cardiovascular mortality became statistically nonsignificant on multivariable adjustment. The trend for higher mortality in patients with 25OHD levels 15–30ng/ml was not statistically significant. Our results indicate there is a graded relationship between serum 25OHD and the risk for death among subjects with chronic kidney disease who are not undergoing dialysis. Randomized, controlled trials are needed to conclusively determine whether vitamin D supplementation reduces mortality.